Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Who Made Your Phone? Compassion and the Voice of the Oppressed in Phone Story and Burn the Boards - Navarro-Remesal, Víctor; Zapata, Beatriz Pérez (Open Library of Humanities, 2018)
Burn the Boards (Causa Creations, 2015) portrays the life of an Indian worker who recycles electronic waste in a precarious environment. Phone Story (Molleindustria, 2011) simulates the journey and process of production and consumption of mobile phones, from Congo and China to Pakistan. Whereas Phone Story is described as ‘an educational game’ that addresses the player directly as a consumer, Burn the Boards is a resource management puzzle that creates compassion through role playing. These games bring to the fore a hidden reality of the everyday that is ingrained in historical relationships and power dynamics, drawing attention to what Michael Rothberg has recognized as ‘exploitation in an age of globalized neo-liberal capitalism’ (2014: iv).  This article explores how these games denounce the smartphone industry by using that same technology. For this purpose, we refer to Game Studies theory on procedural rhetoric; values and ethics; and the role of the player, combined with questions of (neo)colonization, globalization, and neoliberalism drawn from Postcolonial Studies. Our analysis shows the complicity of users and their confrontation with the extreme vulnerability of others, emphasizing how the coloniality of power works in our global consumer society. Thus we study the power relationships described and established by these games, the affective reactions which they seek to trigger, and their potential to transform players from passive observers into ethical players and consumers.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé